Protection of Gentian Violet on Gamma Irradiation in Presence of Certain Additives - Parwate, D.V.; Das Sarma, Indrani (Asian Journal of Chemistry, 2010)
The present work has been carried out to investigate the effect of certain organic compounds on the radiolytic decomposition of gentian violet in aqueous medium. The γ-radiolytic decomposition of the dye solutions of various concentrations were studied at a dose range of 0.040.42 kGy in presence of oxygen and 0.060.59 kGy in an inert atmosphere. The amount of dye decomposed was estimated spectrophotometrically at γmax of 583.0 nm. The protection of the dye was found to be better in absence of oxygen. In case of thiourea and glycerine as additives, the retention of the dye was 100% and as a result the G-value of dye decomposition was found to be zero. In case of glucose and EDTA, the protection of the dye was 90% whereas in case of urea only 70% retention was observed.